2019
DOI: 10.1051/0004-6361/201936478
|View full text |Cite
|
Sign up to set email alerts
|

1:1 orbital resonance of circumbinary planets

Abstract: The recent detection of the third planet in Kepler-47 has shown that binary stars can host several planets in circumbinary orbits. To understand the evolution of such systems we have performed two-dimensional hydrodynamic simulations of the circumbinary disc with two embedded planets for several Kepler systems. In two cases, Kepler-47 and -413, the planets are captured in a 1:1 mean-motion resonance at the planet parking position near the inner edge of the disc. The orbits are fully aligned, have mean eccentri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Even though the gap in the middle panel is only partially opened it already leads to a reduction in orbital eccentricity of the cavity and planet. However, in both cases the planet is still too well embedded in the disc and influenced by its dynamics such that the orbit of the planet and the cavity are fully aligned and precess at the same rate, as also observed in Kley et al (2019); Penzlin et al (2019). For an even lower viscosity of α = 10 −4 (right panel) the planet opens a deeper gap that erases directly the disc driven planet dynamics and allows the planet to reach a stable orbit inside the cavity.…”
Section: The Influence Of Viscositymentioning
confidence: 68%
See 1 more Smart Citation
“…Even though the gap in the middle panel is only partially opened it already leads to a reduction in orbital eccentricity of the cavity and planet. However, in both cases the planet is still too well embedded in the disc and influenced by its dynamics such that the orbit of the planet and the cavity are fully aligned and precess at the same rate, as also observed in Kley et al (2019); Penzlin et al (2019). For an even lower viscosity of α = 10 −4 (right panel) the planet opens a deeper gap that erases directly the disc driven planet dynamics and allows the planet to reach a stable orbit inside the cavity.…”
Section: The Influence Of Viscositymentioning
confidence: 68%
“…Possibly, multiple planets are present in some of the systems that are even slightly inclined so that we see only one of the planets. In Penzlin et al (2019) we showed that a secondary planet does not change the orbit of the first one significantly, hence we did not include multi-planet simulations here.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The models by these authors also show that the formation of a stable co-orbital ring is possible for the Kepler-16 system. Similarly, Penzlin et al (2019) found that co-orbital planets can have stable configurations in the Kepler-47 system. Most recently, Leleu et al (2019) studied the dynamics of a pair of migrating co-orbital planets and showed that depending on the mass-ratio and eccentricities of the planets, and also depending on the type and strength of dissipative forces, the two planets may reside at stable Lagrangian points, may undergo horseshoe orbits, or may scatter out of the system.…”
Section: Introductionmentioning
confidence: 81%
“…14 we can rule out exterior planets larger than 6R ⊕ , and for many of the systems this limit is significantly smaller. We also rule out the commensurate planets predicted by Penzlin et al (2019), unless they are significantly smaller than the detected planet at that period.…”
Section: Searching For Additional Planets In Known Systemsmentioning
confidence: 99%
“…Under certain conditions co-orbital circumbinary planets (i.e. a 1:1 resonance) are predicted by Penzlin et al (2019), to which the algorithm is also sensitive.…”
Section: Searching For Additional Planets In Known Systemsmentioning
confidence: 99%